Basics of Arabic Morphology: Word Structure in Arabic - Ayu Sekar Sari; Johar Kurniawan Siagian; Putri Amelia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Morphology is a branch of linguistics that studies the structure of words and the process of their formation. In Arabic, morphology is known as the science of al-sharf, which examines the roots of words and their formation patterns, both through inflection and derivation. The morphological process includes adding affixes (affixation), modifying word roots, and changing the structure of vowels and consonants to form new words. This research discusses basic concepts of morphology, word structure in Arabic, as well as key terms in morphological processes. The research was conducted using linguistic-based qualitative methods, using a theoretical approach and analysis of Arabic language patterns. The research results show that Arabic morphology has a close relationship between root words, lexemes, morphemes, and words as the final result. It is hoped that this research will contribute to making Arabic language learning easier, both theoretically and practically, as well as enriching linguistic literature in Indonesia.